2015
DOI: 10.1142/s021951941550075x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Test of Human Cerebral Aneurysm Specimens Obtained From Surgical Clipping

Abstract: The walls of the blood vessels involved with cerebral aneurysms present different mechanical properties, when compared with those of normal artery. Consequently the models which may describe then predict an aneurysm rupture need as input their mechanical properties. This paper describes the experimental determination of the mechanical properties of the tissues of the blood vessels affected with a cerebral aneurysm. In particular, we determine and discuss the critical elongation and the rupture strength. The af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…In terms of comparisons, we are able to compare parameter 1 with those obtained in the literature. In (Valencia et al 2015), they extracted from a Mooney-Rivlin hyperelastic model, an average value of parameters 01 + 10 , equivalent to our 1 , of about 0.17 MPa, while in (Toth et al 2007) they found 0.12 MPa. They are of same order than our average value for 1 : 0.11 MPa.…”
Section: Results Analysissupporting
confidence: 46%
See 1 more Smart Citation
“…In terms of comparisons, we are able to compare parameter 1 with those obtained in the literature. In (Valencia et al 2015), they extracted from a Mooney-Rivlin hyperelastic model, an average value of parameters 01 + 10 , equivalent to our 1 , of about 0.17 MPa, while in (Toth et al 2007) they found 0.12 MPa. They are of same order than our average value for 1 : 0.11 MPa.…”
Section: Results Analysissupporting
confidence: 46%
“…Only 7 aneurysms were tested for an average strain rupture limit of 37%. More recently, works of (Cebral et al, 2015) and (Valencia et al, 2015), extracted also rupture limit values from their uniaxial traction tests. In both articles few samples were tested, due to the difficulty of getting aneurysms from surgery.…”
Section: Results Analysismentioning
confidence: 99%
“…The data of various mechanical experiments show significantly different results depending on the method of transportation of the samples, the sensitivity of the used tensile machine and the method of the experiment [3][4][5][6][7]. It was shown [8] that the difference in the mechanical properties of aneurysms among representatives and between samples with different experimental techniques can be comparable. In this regard, the use of coupled tests for the classification of aneurysm tissues becomes important.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of comparisons, we are able to compare parameter C 1 with those obtained in the literature. Valencia et al (2015) extracted from a Mooney-Rivlin hyperelastic model, an average value of parameters C 01 + C 10 , equivalent to our C 1 , of about 0.17 MPa, while…”
Section: Resultsmentioning
confidence: 69%